Effect of metformin on irinotecan-induced cell cycle arrest in colorectal cancer cell lines HCT116 and SW480 - Khader, Esra'a I.; Ismail, Wesam W.; Mhaidat, Nizar M.; Alqudah, Mohammad A. (International Journal of Health Sciences, 2021)
Objectives: Metformin is widely used for the treatment of type 2 diabetes mellitus and found to have a crucial rule in the induction of apoptosis in several cancer types including pancreatic cell carcinoma, epithelial ovarian cancer, breast cancer, and renal cell carcinoma. In this study, we propose to explore the potential role of metformin as an adjuvant of irinotecan to target colorectal cancer (CRC) cell lines, exploring the effects underlying the anticancer properties of metformin on CRC cell lines. Methods: HCT116 and SW480 cell lines were treated with metformin, irinotecan and their combination. The effect of metformin on cell viability was evaluated using MTT assay. Flow cytometry technique was used to analyze apoptosis and cell cycle progression. While, detection of protein expression was analyzed by Western blot. Results: Metformin was found to inhibit growth in both HCT1116 and SW480 cell lines. On combination with irinotecan, it has been revealed that metformin sensitized CRC cells to irinotecan-induced cytotoxicity. Flow cytometry analysis showed that metformin did not induce apoptosis, but blocked cell cycle in G1 and S phases. This blockage was accompanied by decreased cyclin E and Cdk2 levels and increased p21 level. Conclusion: Combination of metformin with irinotecan may be an effective treatment strategy for targeting colorectal cancer that are resistant to irinotecan monotherapy.